Endothelial-specific depletion of TGF-β signaling affects lymphatic function - Kunpei Fukasawa (BMC, 2021)
Abstract Background Transforming growth factor (TGF)-β is a multifunctional cytokine involved in cell differentiation, cell proliferation, and tissue homeostasis. Although TGF-β signaling is essential for maintaining blood vessel functions, little is known about the role of TGF-β in lymphatic homeostasis. Methods To delineate the role of TGF-β signaling in lymphatic vessels, TβRIIfl/fl mice were crossed with Prox1-CreERT2 mice to generate TβRIIfl/fl; Prox1-CreERT2 mice. The TβRII gene in the lymphatic endothelial cells (LECs) of the conditional knockout TβRIIiΔLEC mice was selectively deleted using tamoxifen. The effects of TβRII gene deletion on embryonic lymphangiogenesis, postnatal lymphatic structure and drainage function, tumor lymphangiogenesis, and lymphatic tumor metastasis were investigated. Results Deficiency of LEC-specific TGF-β signaling in embryos, where lymphangiogenesis is active, caused dorsal edema with dilated lymphatic vessels at E13.5. Postnatal mice in which lymphatic vessels had already been formed displayed dilation and increased bifurcator of lymphatic vessels after tamoxifen administration. Similar dilation was also observed in tumor lymphatic vessels. The drainage of FITC-dextran, which was subcutaneously injected into the soles of the feet of the mice, was reduced in TβRIIiΔLEC mice. Furthermore, Lewis lung carcinoma cells constitutively expressing GFP (LLC-GFP) transplanted into the footpads of the mice showed reduced patellar lymph node metastasis. Conclusion These data suggest that TGF-β signaling in LECs maintains the structure of lymphatic vessels and lymphatic homeostasis, in addition to promoting tumor lymphatic metastasis. Therefore, suppression of TGF-β signaling in LECs might be effective in inhibiting cancer metastasis.